Content management model in social media: startups case studies. - Castilho, Ana Sofia (2013)
This study aims to do an exploratory analysis to some startups with a business-to-business approach, in the fields of Information and Communication Technology (ICT), Media and Communication. Fifteen startups, considered the most dynamics in the new media, were engaged in this study. To collect data it was used a script of observation and a survey. Data analysis has shown that contrary to what would be expected for companies operating in this field of activity, its dynamism in new media is reduced. Based on the results it was designed a content management model to be used in the new media, and to be adopted by startups, in order to attract new stakeholders.